Implementasi Kebijakan Kawasan Tanpa Rokok di Rumah Sakit Umum Daerah (RSUD) UNDATA-Palu - Budiwan, Sadry; Arwan, Arwan; Syam, Sadli (An Idea Health Journal, 2021)
RSUD UNDATA Palu is a health service facility that should have 100% to implement the area without cigarettes but until now there are still visitors who do the activity of smoking in the corridor even in the hospital room. Based on Palu City Regulation No. 3 of 2015 on non-smoking areas that are not allowed to engage in smoking activities in areas that have been designated as non-smoking areas, including in health care facilities.